A tadpole-shaped gene carrier with distinct phase segregation in a ternary polymeric micelle1. Issue 14 (14th April 2015) - Chen, Qixian; Osada, Kensuke; Pennisi, Matthew; Uchida, Satoshi; Tockary, Theofilus A.; Dirisala, Anjaneyulu; Li, Yanmin; Takeda, Kaori M.; Oniyanagi, Satoshi; Itaka, Keiji; Kataoka, Kazunori
<x xml:space="preserve">Abstract</x> A tadpole-shaped nanostructure characterized by phase segregation occurring in a single pDNA-containing polymeric micelle is shown.